The neural bases for devaluing radical political statements revealed by penetrating traumatic brain injury - Cristofori, Irene (Soc Cogn Affect Neurosci, 2015)
Given the determinant role of ventromedial prefrontal cortex (vmPFC) in valuation, we examined whether vmPFC lesions also modulate how people scale political beliefs. Patients with penetrating traumatic brain injury (pTBI; N = 102) and healthy controls (HCs; N = 31) were tested on the political belief task, where they rated 75 statements expressing political opinions concerned with welfare, economy, political involvement, civil rights, war and security. Each statement was rated for level of agreement and scaled along three dimensions: radicalism, individualism and conservatism. Voxel-based lesion-symptom mapping (VLSM) analysis showed that diminished scores for the radicalism dimension (i.e. statements were rated as less radical than the norms) were associated with lesions in bilateral vmPFC. After dividing the pTBI patients into three groups, according to lesion location (i.e. vmPFC, dorsolateral prefrontal cortex [dlPFC] and parietal cortex), we found that the vmPFC, but not the dlPFC, group had reduced radicalism scores compared with parietal and HC groups. These findings highlight the crucial role of the vmPFC in appropriately valuing political behaviors and may explain certain inappropriate social judgments observed in patients with vmPFC lesions.